PEMBUATAN SILIKA GEL DARI ABU AMPAS TEBU (Saccharum Officinarum) DAN APLIKASINYA UNTUK ADSORPSI ION Cu (II) - Muhammad Rizky; Alimuddin Alimuddin; Aman Sentosa Panggabean (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
The research of silica gel manufacturing from cane pulp cinders (Saccharum Officinarum) and the application for Cu (II) ion adsorption has been done. The adsorption of Cu (II) ion done by some variaties, such as pH, concentration, and contact time. The result of the research shows the optimum of pH was 8, concentration optimum was 8 ppm, and contact time was 75 minutes. The perecentage of recovery was 90,28%, shows the effectivity of silica gel from cane pulp cinders can be applicated for adsorption Cu (II) ion.